2014
DOI: 10.1021/ac503224j
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Relative Quantitation of Phosphoinositides by Multiple Precursor Ion Scanning Based on Phosphate Methylation and Isotopic Labeling

Abstract: Phosphoinositides, the phosphorylated derivatives of phosphatidylinositol (PtdIns), are key regulators of many fundamental biological processes, including cell growth, proliferation, and motility. Here, we present a novel method for rapid, sensitive, and simultaneous profiling of phosphatidylinositol trisphosphate (PtdInsP3), phosphatidylinositol bisphosphate (PtdInsP2), and phosphatidylinositol phosphate (PtdInsP) of different fatty acid compositions. This method is based on a technique called "charged diacyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…The quantitative analysis of PLs is usually achieved by the inclusion of multiple internal standards (ISDs) and run separately. An alternative strategy for quantifi cation of PLs would be to incorporate a given heavy nuclei (e.g., 2 H, 13 C, or 15 N) into endogenous PLs by metabolic or chemical labeling. Each population of PLs is reacted with a reagent that differs only in its isotopic composition, thereby creating "heavy" and "light" versions of derivatized PLs, which are distinguishable by MS.…”
Section: Lipid Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quantitative analysis of PLs is usually achieved by the inclusion of multiple internal standards (ISDs) and run separately. An alternative strategy for quantifi cation of PLs would be to incorporate a given heavy nuclei (e.g., 2 H, 13 C, or 15 N) into endogenous PLs by metabolic or chemical labeling. Each population of PLs is reacted with a reagent that differs only in its isotopic composition, thereby creating "heavy" and "light" versions of derivatized PLs, which are distinguishable by MS.…”
Section: Lipid Extractionmentioning
confidence: 99%
“…Recently, Nie et al ( 12 ) also demonstrated isobaric mass stable isotope-labeled S,S ′ -dimethylthiobutanoylhydroxysucccinimide ester reagents for characterization and multiplexed quantifi cation of aminophospholipids in biological samples. The advantages of these strategies are that the use of MS2 for by guest, on May 11, 2018 www.jlr.org of individual species in the labeled and unlabeled lipid extracts, respectively, while I labeled and I unlabeled represent the height of the peak of the labeled and unlabeled PL species after 13 C correction, respectively. The results are presented as mean ± SD .…”
Section: Lipid Extractionmentioning
confidence: 99%
See 3 more Smart Citations